The Research on Introduction and Cultivation Mechanism of High-level Talents in Emerging Industries from the Perspective of Toughness Theory - Zhang Liangfei; Huang Yuxi (Government & Resilience, 2025)
Competition in science and technology and manpower has become a key element of global competition. China is vigorously promoting the innovation-driven development policy and the people-centred national talent strategy to seize the commanding heights in the trend of rapid technological advancement and industrial change, and the governments of provinces, cities and counties are focusing on the development of science and technology innovation parks and regional technological innovation centres as a key development strategy in the hope of driving the development of industries through scientific and technological innovations and industry advancement. Based on environmental adaptation, this article systematically studies how to attract and cultivate high-end talents in emerging industries. The article reviews the problems of the traditional mechanism for cultivating high-end talents and summarises the fragile mechanism of the existing mechanism for attracting talents under external impact. Relative to the existing human resource management mechanism, the article provides a high-level four-dimensional resilient talent mechanism for system adaptation, which integrates the four major elements of strategic planning, enterprise linkage, ecosystems and services, and policy adjustment in order to enhance the system's resilience to adapt, flexibility and recovery, and resilience and innovation capabilities. Specific means of realisation include globalised connectivity, enterprise linkage incentives, extension of internet facilities, market-based ecosystem building and regulatory adjustments. A range of measures constitute a system of talent management that can be used to address challenges, effectively adapt to change and maintain forward momentum. This study introduces a new concept of flexibility to the field of public administration, while providing theoretical and operational references for city governments to shift from competing for policy orientation to building an ecosystem in developing human resources for emerging industries.